Sir Ove Arup: The Design of Bridges - Nissen, Jørgen (Docomomo Journal, 2011)
Over Arup (1895-1988) once said in a BBC interview that the two structures that had given him most satisfaction were the Highpoint flats in North London (1935) and the Kingsgate footbridge, Durham, Yorkshire (1963), as “both are rather perfect examples of the complete integration of architecture, structure and method of construction”.